PENGARUH PROMOSI, HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE SHOPEE PADA MAHASISWA UNIVERSITAS HKBP NOMMENSEN MEDAN - Ridhon Simangunsong; Morina (Jurnal Ilmu Sosial Dan Politik, 2021)
This study aims to determine how much influence Promotion, Price and Trust have on Purchasing Decisions in Shopee e-commerce on students of HKBP Nommensen University Medan, either partially or simultaneously.This type of research is quantitative. The population in this study were students of the HKBP Nommensen University, Medan. The sampling technique in this study was simple random sampling with a total sample of 99 respondents.The types of data used are primary data and secondary data. The data collection techniques were questionnaires and observations. The data analysis method used is an instrument test consisting of Validity and Reliability Test, Classical Assumption Test consisting of Normality Test, Multicollinearity Test and Heteroscedasticity Test, Multiple Linear Regression Test and Hypothesis Test consisting of t test, F test, and the coefficient of determination (R2).The results show that promotion has a positive and significant effect on purchasing decisions at e-commerce Shopee, this is indicated by the value of tcount (2.125) > ttable (1.98525) and the significant value of the promotion variable is 0.036 <0.05. Price has a positive and significant effect on purchasing decisions at Shopee e-commerce, this is indicated by the value of tcount (2.097) > ttable (1.98525) and the significant value of the price variable is 0.039 <0.05. Trust has a positive and significant effect on purchasing decisions at Shopee e-commerce, this is indicated by the value of tcount (5.595) > ttable (1.98525) and the significant value of trust is 0.000 <0.05. Simultaneously it is known that Promotion, Price and Trust have a positive and significant effect on purchasing decisions at Shopee e-commerce, this is indicated by the value of Fcount (58.458) > Ftable (2.70) and a significant value of 0.000 <0.05. The coefficient of determination obtained is 0.649, meaning that the purchasing decision variables can be explained by the promotion, price and trust variables of 64.9%. While the remaining 35.1% is explained by other variables that are not included in this model such as product quality, brand image, location, service and so on.